Defining an abnormal p53 immunohistochemical stain in Barrett's oesophagus‐related dysplasia: a single‐positive crypt is a sensitive and specific marker of dysplasia. Issue 4 (16th January 2023) - Tomaszewski, Kristen J; Neyaz, Azfar; Sauder, Kenan; Rickelt, Steffen; Zhang, M. Lisa; Yilmaz, Omer; Crotty, Rory; Shroff, Stuti; Odze, Robert; Mattia, Anthony; Patil, Deepa T; Deshpande, Vikram
Abstract : Aims: p53 is an independent risk stratification marker in Barrett's oesophagus (BE), but no universally accepted definition exists for abnormal p53 staining. Herein, we assess p53 stains in two cohorts to: (1) define abnormal p53 staining in BE‐related dysplasia (BERD) and (2) assess the specificity and sensitivity of this cut‐point for the diagnosis of dysplasia. Methods: Cohort 1 ( n  = 313) included (1) dysplastic BE biopsies, (2) prior non‐dysplastic BE (NDBE) biopsies from the same patients and (3) NDBE biopsies from patients who never progressed to dysplasia. Cohort 2 ( n  = 191) consisted of BE biopsies in which p53 staining aided in diagnosing dysplasia. Automated p53 staining quantification was performed on cohort 1. A semiquantitative p53 analysis, performed on both cohorts, included: (1) number of strongly positive glands, (2) strong glandular surface staining, (3) percentage of strongly positive glands and (4) null phenotype. Results: NDBE biopsies from cohort 1 patients who progressed to dysplasia were more likely to show p53 positivity than non‐progressors (16.9 versus 0.6%) ( P  = 0.0001). The optimal quantitative cut‐point for distinguishing dysplastic from never‐dysplasia biopsies was 10 strongly positive cells. By semiquantitative analysis, a single strongly p53‐positive gland distinguished dysplastic from never‐dysplasia BE (sensitivity 98.6%, specificity 99.4%). The semiquantitative and quantitative analyses correlated ( P  = 0.0001). In cohort 2, the sensitivity and specificity for BERD of ≥ 1 strongly positive p53 gland were 86.0 and 88.6%. Conclusions: A single strongly positive p53 gland is sensitive and specific for BERD. Automated p53 analysis may reduce subjectivity associated with the diagnosis of BERD. Abstract : Figure 1: Study design of cohort 1. The figure also highlights the results of the analysis performed on cohort 1.